Rorschach Assessment in Suicide Survivors: Focus on Suicidal Ideation - Palmieri, Arianna; Kleinbub, Johann Roland; Mannarini, Stefania; Molinaro, Sara; Castriotta, Cristina; Scocco, Paolo (Frontiers in Public Health, 2019)
Background: The study of Suicidal ideation (SI) in people bereaved through suicide (Suicide Survivors - SSs) could be hampered by the person’s willingness to admit it, or by their limited awareness of it. Our main hypothesis is that SI is common in these people, especially if they are parents or children of the victim. For its potential in shedding light on specific unconscious processes, Rorschach test was chosen for our investigation, for the first time in SSs literature. Rorschach suicide ideation and selected variables were further analyzed to better delineate their psychological profile. Method: Rorschach according to Exner’s Comprehensive System was administered to 21 people bereaved through suicide presenting as outpatients at SOPROXI Project Service –Padova Mental Health Center- and 23 healthy controls. Beck Depression Inventory was routinely administered to SSs and considered in the study. Results: T-tests showed significantly higher mean SI score (S-Con) as it emerged from the Rorschach test S-Con scores in SSs compared to control participants. SI found only weak correlation with the BDI item in which SSs can explicitly state the desire for their death. Within-group analysis revealed higher S-Con mean scores in bereaved children and parents of the victim compared to other kind of kinships. Morbid content (MOR) has been fund as the most characterizing variable in SSs’ S-Con in terms of effect size, followed by a low number of responses with an ordinary form (X +%). Human movements (M), Special Scores related to thought slippage (ALOG, FABCOM2, INCOM2 and CONTAM) and poor human representations (PHR) have been shown to be more significantly present in SSs compared controls. Discussion. Psychodynamic interpretations of our results are provided. Clinical practice should consider Rorschach as one of eligible tools of investigation on this field.